Implications for Cation Selectivity and Evolution by a Novel Cation Diffusion Facilitator Family Member From the Moderate Halophile Planococcus dechangensis - Xu, Tong; Chen, Huiwen; Li, Jincheng; Hong, Shan; Shao, Li; Zheng, Xiutao; Zou, Qiao; Wang, Yuting; Guo, Sijia; Jiang, Juquan (Frontiers in Microbiology, 2019)
In the cation diffusion facilitator (CDF) family, the transported substrates are confined to divalent metal ions, such as Zn2+, Fe2+, and Mn2+. However, this study identifies a novel CDF member designated MceT from the moderate halophile Planococcus dechangensis. MceT functions as a Na+(Li+, K+)/H+ antiporter, together with its capability of facilitated Zn2+ diffusion into cells, which have not been reported in any identified CDF transporters as yet. MceT is proposed to represent a novel CDF group, Na-CDF, which shares significantly distant phylogenetic relationship with three known CDF groups including Mn-CDF, Fe/Zn-CDF, and Zn-CDF. Variation of key function-related residues to “Y44-S48-Q150” in two structural motifs explains a significant discrimination in cation selectivity between Na-CDF group and three major known CDF groups. Functional analysis via site-directed mutagenesis confirms that MceT employs Q150, S158, and D184 for the function of MceT as a Na+(Li+, K+)/H+ antiporter, and retains D41, D154, and D184 for its facilitated Zn2+ diffusion into cells. These presented findings imply that MceT has evolved from its native CDF family function to a Na+/H+ antiporter in an evolutionary strategy of the substitution of key conserved residues to “Q150-S158-D184” motif. More importantly, the discovery of MceT contributes to a typical transporter model of CDF family with the unique structural motifs, which will be utilized to explore the cation-selective mechanisms of secondary transporters.